CONTENT WORDS IN INSERTIONAL CODE MIXING BY ENGLISH STUDENTS - Nurma Dhona Handayani; Robby Satria (JEE (Journal of English Education), 2018)
Mixing of the language is the insertion of a word or phrase of one language to other language where one language as a base or matrix language. A person who has mixed is if he or she uses a word or phrase from another language. Otherwise, the phenomenon of mixing occurs, if a person uses one clause which has the grammatical structure of one language and after that, it is constructed based on the grammar of another. The phenomena of code-mixing can also occur in English students‟ communication. Therefore, this research aims to find out what is content word‟s in insertional code-mixing found in the utterances of the English Department students of Putera Batam University in Batam, Riau Islands. Analysis of the data referring to the code-mixing typology of utterances that led to the insertion of the characteristics of the intervention code (insertional code-mixing) between Indonesian and English based on the code-mixing typology proposed by Pieter Muysken.